L2 classroom contexts: deviance, confusion, grappling and flouting. Issue 1 (2nd January 2019) - Seedhouse, Paul
ABSTRACT: Seedhouse (2004) suggested that L2 classroom interaction can be understood in terms of sub-varieties or L2 classroom contexts. These are the 'interfaces' between pedagogy and interaction in which a particular pedagogical focus combines with a particular organisation of the interaction. However, Conversation Analysis does not see such organisations as a fixed set of prescriptive rules, but as interpretive resources which speakers make use of in order to orientate themselves. Deviant cases are particularly illuminating, so here we look at four kinds of deviant cases in relation to L2 classroom contexts. In the first, teachers and learners grapple for the direction of the pedagogical focus and hence the kind of context which is established. In the second, there is confusion amongst participants as to which context is in operation. In the third type of case we see inexperienced trainee teachers failing to establish a pedagogical focus and L2 classroom context. In the fourth we see experienced teachers deliberately 'flouting' the normal organisation of the L2 classroom in order to achieve particular effects. Implications are that L2 classroom contexts are interactional organisations which are actively constructed and maintained by experienced teachers. Microanalysis can help trainee teachers see what can go wrong, as well as how to get it right.